Gas flaring Effects around Agbada II Flow Station in Igwuruta, Rivers State, Nigeria - Chukwu, Maureen N. (University of Thi-Qar Journal of Science, 2022)
The levels of pollutants around Agbada II Flow Station were investigated. Four sampling stations (A – D) located 500 m apart in the downwind direction and a control located 3.5 km in the upwind direction were monitored. The results showed that the air pollutant parameters varied as follows carbon monoxide 1.20 – 2.40 (1.80 ± 0.13), sulphur dioxide 0.00 – 0.01 (0.005 ± 0.001), Volatile Organic Compounds (VOC) 0.00 – 0.01 (0.002 ± 0.001 ppm), Hydrogen Sulphide (H2S) 0.001 – 0.001 (0.001 ± 0.0004 ppm), Ozove (O3) 0.01 – 0.01 (0.01 ± 0.005) and suspended particulate matter (SPM) 32.00 – 40.20 (36.10 ± 1.75) parts per million (ppm). The heavy metals in soil; lead (Pb) 0.01 – 0.80 (0.38 ± 0.07ppm), nickel (Ni) 70.00 – 80.20 (75.41 ± 3.68ppm), cadmium (Cd) 0.00 – 0.30 (0.05 ± 0.022 ppm), Cobalt (Co) 0.00 – 0.40 (0.08 ± 0.02 ppm), Copper (Cu) 1.20 – 2.30 (2.00 ± 0.16 ppm), Iron (Fe) 0.00 – 0.50 (0.10 ± 0.04 ppm), Zinc (Zn) 0.01 – 0.01 (0.01 ± 0.001 ppm), and meteorological parameters; wind speed 0.20 – 0.30 (0.26 ± 0.013) m/s, ambient temperature 28.6 – 36.4 (32.25 ± 0.188) ºC, relative humidity (RH) 70.00 – 75.00 (72.33 ± 1.72) %. There was a significant spatial difference in the mean values of the ambient air parameters at P < 0.05 and SPM contributed to the difference, though there were no significant correlations between levels of heavy metals.